Reinforced falsetto to increase the glottic closure in patients diagnosed with unilateral vocal cord paralysis - Patricio Orellana Marambio; Felipe Gonzalo Rosales Lillo; Giovanna Monichi Valdenegro (Revista de Investigación en Logopedia)
There is favourable evidence in speech therapy for the rehabilitation of vocal cord paralysis. Nonetheless, contemporaneous studies that apply reinforced falsetto were not found. The aim of this study is to determine the results of speech therapy using reinforced falsetto for complete glottic closure in patients diagnosed with unilateral vocal cord paralysis, who were treated at the Laboratory of Voice at the ‘Universidad del Desarrollo’ in Chile between 2015 and 2023. A descriptive, observational and retrospective study was performed on 10 adult participants. Before therapy, dysphonia was severe in 90% of the participants, whilst moderate in the remaining 10%. Incomplete glottic closure was observed in 100% of the participants. After the therapy, dysphonia was diagnosed as being mild in 60% of the cases, and normal in the remaining 40% of participants. All the participants recovered their glottic closure. Significant differences were observed pre-intervention and post-intervention in: fundamental frequency (p .028); sound intensity (p .006); harmonics (p .000); maximum phonation time (p .000); glottic closure (p .002); and dysphonia severity (p .004). In conclusion, the reinforced falsetto technique was favourable for the glottic closure in the sample of participants studied. Further, there was clinical improvement in all the analysed variables. Speech therapy using reinforced falsetto   could therefore be useful for the rehabilitation of unilateral vocal cord paralysis. It is suggested that extra research is performed, including a representative sample, in order to generalise the results and make them applicable to the general population.